Bis{2-methoxy-6-[(E)-(4-methylbenzyl)-iminomethyl]phenolato}palladium(II) chloroform monosolvate - Bahron, Hadariah; Mohd Tajuddin, Amalina; Wan Ibrahim, Wan Nazihah; Suchada, Chantrapromma; Fun, Hoong Kun (International Union of Crystallography, 2014)
In the title complex, [Pd(C16H16NO2)2]CHCl3, the PdII cation lies on an inversion center. One Cl atom of the CHCl3 solvent molecule lies on a twofold axis and the C—H group is disordered with equal occupancies about this axis with the other Cl atom in a general position with full occupancy. The PdII cation is four-coordinate and adopts a square-planar geometry via coordination of the imine N and phenolic O atoms of the two bidentate Schiff base anions. The N and O atoms of these ligands are mutually trans. The plane of the benzene ring makes a dihedral angle of 73.52 (10) with that of the methoxyphenolate ring. In the crystal, molecules of the PdII complex are arranged into sheets parallel to the ac plane, and the chloroform solvent molecules are located in the interstitial areas between the complex molecules. Weak intermolecular C—H O and C—H interactions stabilize the packing.